Therapeutic Whole Lung Lavage for Pulmonary Alveolar Proteinosis: Technique With Continuous Video‐Enabled Double Lumen Endotracheal Tube - Kevin Davidson (Respirology Case Reports)
ABSTRACT Therapeutic whole lung lavage with a continuous video‐enabled double‐lumen endotracheal tube improves the safety of therapeutic whole lung lavage in autoimmune pulmonary alveolar proteinosis.